High-Resolution Imaging with (99m)Tc-Glucarate for Assessing Myocardial Injury in Rat Heart Models Exposed to Different Durations of Ischemia with Reperfusion - Liu, Zhonglin (2004)
(99m)Tc-Glucarate ((99m)Tc-GLA) is a novel infarct-avid imaging agent. The aim of this study was to evaluate the role of (99m)Tc-GLA for assessing the severity of myocardial ischemia—reperfusion injury in rat heart models exposed to varied durations of left coronary artery (LCA) occlusion with reperfusion using a high-resolution SPECT system, FASTSPECT. We also wanted to clarify whether a rapid sequence of 3-dimensional imaging with FASTSPECT can quantify uptake and washout kinetics of cardiovascular imaging agents in small-animal heart models. METHODS: The ischemic—reperfused rat heart models were created by ligating the LCA for 30 min (IR30, n = 12) or 90 min (IR90, n = 6) (IR = ischemia—reperfusion) and releasing the ligature for 30 min. Dynamic images were acquired over a 2-h period after (99m)Tc-GLA was intravenously injected. The ischemic area at risk (IAR) was determined by Evans blue staining. Necrosis was assessed with triphenyltetrazolium chloride (TTC) staining and a transmission electron microscope (TEM). RESULTS: The infarct size of the left ventricle (% IAR) on TTC staining was smaller in IR30 (49.2 ± 4.3) than in IR90 (73.4 ± 4.7, P < 0.05), which exhibited evidence of more severe irreversible injury than the IR30 heart on TEM. FASTSPECT images demonstrated hot spot accumulations of (99m)Tc-GLA in all hearts. The washout of (99m)Tc-GLA from the ischemic—reperfused area in IR90 was significantly slower than that in IR30. The ratio of the hot spot to normal myocardial activity was 4.1 ± 0.3 in IR30 and 7.1 ± 1.1 in IR90 (P < 0.05). The hot spot size (% IAR) (58.4 ± 2.7 in IR30 vs. 75.9 ± 2.7 in IR90, P < 0.05) related significantly to the infarct size. CONCLUSION: The severity of myocardial injury induced by ischemia—reperfusion can be assessed by FASTSPECT imaging with (99m)Tc-GLA. The results suggest that (99m)Tc-GLA will be clinically useful in detecting and quantifying acute necrotic myocardium. The FASTSPECT imaging with the rat heart models provides a solution-specific approach with high-resolution and fast dynamic acquisition for kinetic studies of new myocardial imaging agents.